Impact of Mandatory IFRS Adoption on Economic Growth: The Moderating Role of Covid-19 Crisis in Developing Countries - Azzouz Elhamma (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Question- Does Covid-19 crisis moderate significantly the relationship between mandatory International Financial Reporting Standards (IFRS) adoption and economic growth in developing countries, especially in the MENA (Middle East and North Africa) region and SSA (Sub-Saharan Africa) countries? Motivation- Two sources of motivation are behind this study. First, research works on the impact of mandatory IFRS adoption on macroeconomic indicators such as economic growth are still scarce. Second, studying the impact of mandatory IFRS adoption on economic growth before and during the Covid-19 crisis allows to better understand this relationship in times of crisis. Idea- This article aims to investigate the moderating role of Covid-19 crisis in the relationship between mandatory IFRS adoption and economic growth in developing countries. Tools- The study was conducted based on panel data from 30 developing countries (15 MENA countries and 15 SSA countries) during the period 2017–2020. Collected data were analysed by using the Generalized Least Squares (EGLS/weighted cross-section) with fixed effect estimation technique. Findings- The main results of the study show that mandatory IFRS adoption has a positive impact on economic growth of the full sample, and that this positive impact is reduced during Covid-19 crisis. Contribution- The study results are very useful to policymakers and regulators in developing countries, especially in crisis periods.
Keywords: M41; 650; Mandatory IFRS adoption; Economic growth; Covid-19 crisis; developing countries; MENA region; Sub-Saharan Africa